Measuring systemic risk of Greek banks: New approach by using the epidemic model “SEIR” - Abdelkader Derbali; Slaheddine Hallara (Cogent Business & Management, 2016)
In the last decade of the financial crisis of 2007, the international financial system appeared to be on the brink of a major systemic crisis which leads to a failure of a systemically important European bank. This type of scenario highlights the need for identifying and measuring of the contribution of banks to systemic risk in the financial system. Then, the aim of this paper is to propose, for the first time, a new approach to measure systemic risk in the financial institutions. This approach is based on the epidemic model methodology. Then, we use the SEIR model with four compartments: Susceptible, Exposed, Infected, and Removed. We apply this model for a sample of 18 Greek banks listed in the Athens Exchange over the period from 2 January 2006 to 31 December 2012. Based on the empirical results, we find the existence of 12 times of default transmission during the study period and the transmission of default coincides with the number of Greek banks that have declared failure and then leaving the Athens Exchange. Also, we remark that the continuation of aid and recovery plans granted by international and national regulatory authorities did enough to save Greek banks.
Keywords: 650